Pertanggungjawaban dan Penyelesaian Sengketa Konsumen Berkaitan Dengan Perdagangan Parsel - Kadek Purwa Sastra Diyatmika; Ida Ayu Putu Widiati; Ni Made Sukaryati Karma (Jurnal Analogi Hukum, 2020)
Abstract—This is a consumer protection guarantee which should be by the consumer over any food products purchased from manufacturers or businessmen. For businessmen who just always worried about how to gain that much without thinking of the interests of consumers. It can be posed some problems that would constitute the subject of this research, the problem namely: 1) how form of liability in case of loss on consumers due to consume products in parcels. 2) how does the dispute resolution mechanism that creates consumer losses resulting from consuming products in parcels. This presentation method using empirical legal research, sociological issues in IE approach using an approach based on the provisions of the law and legal developments on a periodic basis. Liability in the event of the occurrence of harm on consumers due to consume products in parcel is a party – the party that made a mistake and led to losses. Parties – parties that are manufacturer, businessmen and parcel delivery service. Sanctions according to the civil code, namely compensation or administrative sanction and according to the criminal law, namely criminal confinement 5 years in prison. Consumers are dispute resolution mechanism gives rise to loss due to consume products in gifts can be made in litigation or non litigation. In trade parcels expected all parties to know about their respective responsibilities so that would not be incurred losses against consumers who consume parcels.